A single-center pilot randomized controlled trial of atorvastatin loading for preventing ischemic brain damage after carotid artery stenting - Wang, Haipeng; Wang, Junjie; Qi, Peng; Yang, Ximeng; Chen, Kunpeng; Hu, Shen; Liu, Erteng; Zhang, Shun; Gao, Qun; Li, Rui; Lu, Jun; Deng, Gang; et al. (Frontiers in Aging Neuroscience, 2022)
Objective Carotid artery stenting (CAS) performed perioperatively with high-dose atorvastatin may reduce the incidence of new ischemic brain lesions, but more high-level evidence is needed. Furthermore, the optimal dose and course of perioperative statin therapy remain uncertain. Methods A single-center, prospective, parallel controlled, pilot randomized clinical trial was conducted at Beijing Hospital. The study includes a total of 130 patients with CAS. The patients were randomly assigned to receive a high-dose of 80 mg/day atorvastatin (n = 65) or a standard-dose of 20 mg/day atorvastatin (n = 65) 3 days before and 3 days after planned CAS. The primary endpoint event was the cumulative incidence of silent new ischemic cerebral lesions (sNICL) on post-CAS cerebral diffusion-weighted magnetic resonance imaging (DW-MRI), transient ischemic attack (TIA), or ischemic stroke within 30 days after CAS. Results Among the 130 patients, 123 completed the study, of which 63 were in the high-dose group and 60 were in the standard-dose group. The incidence of major endpoint events was 69.8% (44 cases) and 78.3% (46 cases) in the high-dose and standard-dose groups, respectively. There was no significant difference between the two groups (HR, 0.705; 95% CI, 0.315–1.576; p = 0.393). According to the stratified analysis results, the sNICL incidence was significantly different between the two groups in the symptomatic patients (HR, 0.263; 95% CI, 0.70–0.984; p = 0.04). Conclusion Among patients with CAS, a periprocedural high-dose of atorvastatin did not reduce the rate of periprocedural ischemic brain damage. However, high-dose statins can reduce the incidence of sNICL after CAS in patients with symptomatic carotid stenosis. Clinical Trial Registration Clinicaltrials.gov, identifier NCT03079115.